Register Used in Reptile Lovers Facebook Forum - Faraz, Hammam Azka; Ariyanti, Lisetyo (Language Horizon: Journal of Language Studies, 2021)
There are three objectives in this research, first, to clarify the form of language and the type of register used by members of the reptile lovers Facebook forum. Second, to identify the register function in the content of a word or phrase. Third, to find out the meaning of the registers found. The type of this research is qualitative research. This research uses documentation from the Facebook forums. The source of the data for this research is a collection of discussion threads from several forums. The results of this study are that the language forms of register used in the forums are nouns (6 data), verbs (5 data), adjectives (1 data), noun phrases (1 data), and prepositional phrases (2 data). The register type that is used in the forum is Casual Register because it is between the members in the forum in an informal situation. The function of the register is the Instrumental, Personal, and Heuristic Register.